الشيخ محمد بن عبد الرسول البرزنجي وجهوده العلمية - أحمد, ئوميد عثمان (Sulaimani Journal for Humanities, 2018)
Sheikh Muhammed Abdul-Rasul al-Barzinji was one of the great Muslim scholars who lived in the eleventh century of Islamic calendar (seventh century AD). He was born in Barzinja village in south of great Kurdistan. In his birth place, he studied many Islamic sciences and principles. Then, he left Barzinja for ever and settled in Madinah, in 1068 Hijiri. After a short period of his settlement, he became a well-known and famous scholar in Madinah. Hundreds of Islamic Students jointed his lessons and they got certificates from him. Although al-Barzinji was following Shafi’i school in Islamic jurisprudence, he was Ash’ari in schools of thought. He was also under the impact of Sufism but he had own and independent viewpoints on the issues and he had own Ijtihad (independent reasoning in Islamic Law) at that time. In his Ijtihad, he only followed the strong and realistic evidence. Al-Barzinji had written nearly 90 books in Arabic, Persian and Turkish languages in sciences of Tafseer (Exegesis), Kalam (Islamic scholastic theology), Tasawf 101 (Mysticism), linguistic, jurisprudence and Hadiths (Prophetic Traditions). Twelve of these books has been printed yet, while the others books are still scripts and kept in the famous European and Islamic libraries.In 1103 Hijri (1691 AD), Al-Barzinji passed away in Madinah and was buried in an area in the Baqi’. Later this area was called ‘the grave of Sadat al-Barzinji’.